Effect of Lorentz Force on Motion of Electrolyte in Magnesium Electrolysis Cell - Cheng-Lin Liu; Ze Sun; Gui-Min Lu; Xing-Fu Song; Jian-Guo Yu, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Magnesium production process is highly energy intensive. Electrolysis process provides an effective route to reduce the energy consumption. In this paper, a three-dimensional electro-magneto-hydrodynamics coupling model of a 120 kA magnesium electrolysis cell using finite element method is presented. In this model, the electric field, magnetic field, and flow field are included. This paper concerns the effects of the Lorentz force on the motion of the electrolyte in the cell. The model predicts that the magnitude of Lorentz force is at its maximum near the region between the anode and cathode. The direction of the Lorentz force is beneficial to the motion of the electrolyte in the magnesium electrolysis cell.